Splinter removal with the aid of ultrasonography: a case report - Lee, C.K.; Ahmad, T.S.; Abdullah, B.J. (Malaysian Orthopaedic Association, 2008)
Splinter or foreign body removal from the hand and foot is a common occurrence. Usually only the deep seated, broken or missed splinters are referred to the surgeon for removal. Unless the object is radio-opaque, plain radiograph will not give any useful information, hence removal can sometimes be very difficult and traumatic. We are reporting a case where a radiolucent splinter was removed with the aid of ultrasonography. This modality can help to localize a splinter at the pre and intra-operative period, minimizing amount of exploration and time of operation.